2019
DOI: 10.1111/joes.12304
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive Taxation Methods: A Review of the Empirical Literature

Abstract: This paper reviews the empirical literature studying the effect of the introduction of presumptive taxation methods on taxpayers’ behavior. Although the concept of presumptive taxation entails numerous alternative methods to determine tax liabilities, I survey two main areas of the literature: indirect tax assessment methods and presumptive minimum taxes. The review investigates efficiency and equity implications of presumptive taxation methods. Conflicting conclusions emerge about the effectiveness of presump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
(100 reference statements)
1
20
0
1
Order By: Relevance
“…L'expérience de l'Espagne, par exemple, semble indiquer que la sous-déclaration des revenus est beaucoup plus répandue chez les indépendants que chez les salariés (Martinez-Lopez, 2012 [26]). Les observations relatives à d'autres pays confirment que les travailleurs indépendants sous-déclarent fréquemment leurs revenus d'activité (Hurst, Li et Pugsley, 2010[27] ; Bucci, 2019 [28]). Aux États-Unis, selon une enquête de 2018, 32 % des indépendants sous-déclarent incontestablement leurs revenus à des fins fiscales (Bruckner et Hungerford, 2019[29]).…”
Section: Validation Des Revenus Pouvoir De Négociation Et Variabilitunclassified
“…L'expérience de l'Espagne, par exemple, semble indiquer que la sous-déclaration des revenus est beaucoup plus répandue chez les indépendants que chez les salariés (Martinez-Lopez, 2012 [26]). Les observations relatives à d'autres pays confirment que les travailleurs indépendants sous-déclarent fréquemment leurs revenus d'activité (Hurst, Li et Pugsley, 2010[27] ; Bucci, 2019 [28]). Aux États-Unis, selon une enquête de 2018, 32 % des indépendants sous-déclarent incontestablement leurs revenus à des fins fiscales (Bruckner et Hungerford, 2019[29]).…”
Section: Validation Des Revenus Pouvoir De Négociation Et Variabilitunclassified
“…Tax evasion is an urgent challenge for many governments (Bucci, 2020;Mocanu, 2020;Herbain, 2018;Dobrovič et al, 2017;Castro & Camarillo, 2014). Theoretically, in laboratory conditions, the following statement could be applied: tax revenues enable to ensure adequate infrastructure, health, education, culture, employment, social income distribution, and public safety.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of tax fraud as a serious social and economic challenge of this time thus requires a complex and especially conceptual approach of all interested state bodies and other entities (Bucci, 2020;Mocanu, 2020;Srn-ková, 2014). This extensive empirical research, its results and the recommendations specified in more detail in the following chapters of this paper aim to make a contribution to this goal.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from Spain, for instance, suggests that income underreporting is much more common among the self-employed than among employees (Martinez-Lopez, 2012 [25] ). Findings from other countries confirm that the self-employed often underreport their earnings (Hurst, Li and Pugsley, 2010 [26] ; Bucci, 2019 [27] ). In the United States, a 2018 survey found that 32% of self-employed admittedly underreport their income for tax purposes (Bruckner and Hungerford, 2019 [28] ).…”
Section: Income Validation Bargaining Power and Income Variabilitymentioning
confidence: 84%
“…In Germany, while there is no minimum earnings requirement, workers with a monthly income of 450 EUR or less (so-called "minijobbers") have the possibility to opt out of the statutory pension insurance. 27 Nineteen countries require neither a minimum level of earnings nor a minimum number of hours, i.e. all part-time workers are covered by pension schemes.…”
Section: Part-time Workmentioning
confidence: 99%